2022
DOI: 10.1111/pde.14982
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in telemedicine use during the COVID‐19 pandemic among pediatric dermatology patients

Abstract: Background/Objectives The COVID‐19 pandemic necessitated rapid implementation of telemedicine at medical centers across the United States. As telemedicine is expected to persist beyond the pandemic in subspecialties like pediatric dermatology, there is growing concern that socioeconomic factors may contribute to inequitable telemedicine access. This study aims to identify factors associated with disparities in telemedicine use among pediatric dermatology patients during the pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…Our finding that NEPL patients are less likely to utilize synchronous teledermatology is in concordance with previously published studies. [2][3][4][5] This suggests our system did not initially have processes to support telehealth access for these patients. This was identified as a digital equity factor when telehealth use grew in 2020, and shortly after this study period, our system added bilingual patient-facing technical support staff and a process for directly dialing-in interpreters during video encounters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that NEPL patients are less likely to utilize synchronous teledermatology is in concordance with previously published studies. [2][3][4][5] This suggests our system did not initially have processes to support telehealth access for these patients. This was identified as a digital equity factor when telehealth use grew in 2020, and shortly after this study period, our system added bilingual patient-facing technical support staff and a process for directly dialing-in interpreters during video encounters.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is growing concern that under‐resourced populations may be left behind with the adoption of telehealth. Prior single‐center retrospective studies identified that non‐English primary language (NEPL), lower income, and public insurance type were associated with less engagement in synchronous teledermatology 2–5 . Findings regarding race were mixed, with some studies showing higher engagement of minority, and specifically Black, patients, in the COVID era, 3,5 while another found less telehealth utilization among Black patients 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A US study comparing pediatric teledermatology visits scheduled post–COVID-19 with in-person appointments in the same period pre–COVID-19 reported that certain demographic groups such as Spanish-speaking patients were less likely to have teledermatology visits [ 21 ]. Another single center US study [ 22 ] demonstrated via multivariate analyses that independent factors associated with lower rates of telemedicine use were patients identifying as Black/African American and having a non-English preferred language. In this study, patients on public insurance were also found to have significantly lower odds of telemedicine use despite widely expanded telehealth coverage by US health insurance plans.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic data associated with digital inequity may be an indicator of the likelihood to complete teledermatology visits. Patients greater than 65 years of age, those who reported a non-English language as their primary language, and participants with lower income were less likely to complete teledermatology visits compared to their counterparts [5,6,8,9]. Other studies noted patients older than 65 years and those reporting lower income were less satisfied with the visit experience [10][11][12].…”
Section: Demographic Data Associated With Digital Inequitymentioning
confidence: 98%
“…Demographics that report less access to broadband internet and technology recorded lower telehealth utilization rates during the COVID-19 pandemic. For instance, older age and persons who reported a non-English language as their primary language were associated with fewer completed telemedicine visits [4][5][6]. Inequity in access to telemedicine care exists.…”
Section: Introductionmentioning
confidence: 99%